INCIDÊNCIA DE BIPOLARIS SOROKINIANA NAS SEMENTES E A TRANSMISSÃO PARA PLANTAS DE CEVADA - Ferrari, Josiane Takassaki (Scientia Agraria, 2003)
The yield potential of barley is reduced mainly because of diseases such as helminthosporiosis or spot blotch caused by Bipolaris sorokiniana (Sacc. in Soroc.) which is seed transmitted. The hypothesis of this study is that the seed is the principal means of disease dissemination and thus, different levels of the fungus incidence in seeds could be related with its incidence on plants originated from those seeds. The objectives of the work were: to study the correlation among different levels of seed infection and its transmission to barley plants under field and greenhouse conditions, and determine the capacity of seed transmission of the fungus. Barley seeds cv BR-2 naturally infected with the levels of 2.7; 7.5; 12.5; 16.5; 31.0 and 55.5 % of the fungus were sown in the field, with four replications. The evaluation of disease seedling showing symptoms of helminthosporiosis and its percentage in relation to the seed emergence, were made seven days after emergence. In greenhouse, seeds were sown in plastic trays containing with approximately 13 kg of soil previously sterilized with dazomet. Four hundred seeds of each treatment (infection level) were planted and covered with 3 cm of soil (3 cm depth). The importance of the infected seeds as a source of primary inoculum was demonstrated. It was observed that on the field the transmission of the pathogen was more efficient when the seed infection level was 55 %. On the other hand, in greenhouse there was correlation only between seed infection and roots. In conclusion, there was no correlation among the seed infection levels of B. sorokiniana and their incidence in the field, and seed infection levels of 55 % reduce seedling emergence both, in the field or in greenhouse.